ILLOCUTIONARY ACTS ANALYSIS OF THE MAIN CHARACTER IN “BRAVE” MOVIE - Elvita Savitri Dewi; Raudlotul Jannah (Universitas Galuh, 2022)
This paper investigates the illocutionary acts used by Merida as the main character in Brave movie published by Walt Disney Pictures. In this paper, the problem to be solved: (1) What types of illocutionary acts are used by the main character in the Brave movie? (2) What types of illocutionary acts are dominantly used by the main character in the Brave Movie? This paper uses the qualitative descriptive approach to describe and analyze the illocutionary utterances uttered by the main character in that movie. This paper focused on the illocutionary acts proposed by Searle (1979). There are five types of illocutionary acts found in this paper: representative, directive, expressive, commissive, and declarative. This paper found 58 utterances produced by Merida, which consisted of illocutionary acts. There are thirty-two (32 times or 55.2%) representative acts, five (5 times or 8.6%) expressive, sixteen (16 times or 27.6%) directive, four (4 times or 6.9%) commissive, and the least frequently used is the declarative illocution which appears in only one (1 time or 1.7%) utterance. This paper concludes that the most dominant representative acts appear in Merida’s utterances that a total of 55.2% frequently used. The researcher recommends this research be used as a reference for learning in the context of a language and determining the purpose of speech or language in linguistics, especially pragmatics.